PERAN UKM DALAM MENSTABILKAN HARGA MASKER SEBAGAI BENTUK PENCEGAHAN PENYEBARAN COVID-19 DI BANDA ACEH - Arfan, Rahmat; Hamdani, Hamdani; Puspita, Desy; Akbar, Indra; ambartiasari, Geta; Mirnawati, Mirnawati (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2020)
Community Service Activities (PkM) aim to help ease the burden on people affected by Covid-19 in Banda Aceh. This activity has resulted in a caring attitude towards people who need masks at affordable prices. Meanwhile, the price of masks has been influenced by market mechanisms. By empowering micro, small and medium enterprises (SMEs) to produce masks made of cloth, the availability of masks in the market has reduced scarcity so that prices are stable. The method of implementing this activity is direct application in the field.